Immunohistochemical assesment of etanol induced dangerof hepatocytes’ damage - Pedrycz, Agnieszka; Siermontowski, Piotr; Polz, Dorota; Ciechan, Alicja; Kocki, Janusz; Puchalska-Kosiecz, Agnieszka (Current Problems of Psychiatry, 2011)
Biodegradation of ethanol takes place mainly in the liver and liver is the most exposed to alcohol and its metabolite acetaldehyde. Free radicals and oxygen stress are responsible for alcohol induced destructions of the liver. Free radicals induce peroxidation of membranous lipids and increase membranes’ permeability.In present study we evaluated in immunohistochemical way expression of HSP 70 protein – biomarker of early ethanol induced danger in the cells. We examined an influence of time and dose of alcohol on HSP70 expression.The study material consisted of white Wistar male rats divided into 5 equal groups – 8 individuals each Experimental groups: rats received per os single dose of 0,5 ml 40% ethanol and were decapitated after 1, 3, 8 and 12 hours. Control group: 8 rats decapitated after 1, 3, 8 and 12 hours of experiment – 8 individuals. Specimens of liver were examined using standard three-step immunohistochemical method to detect HSP70.Single dose 0,5 ml of ethanol given to 300 g rats is similar to single dose 130ml of given to 80 kg men. One hour after such a dose the concentration in blood is 0,95‰, after 3 hours 0,6‰ and after 8 hours alcohol is eliminated from blood. Results in present study show that HSP70 takes part in protection of hepatocytes’ proteins against ethanol induced toxicity. Expression of HSP70 increased in one hour after dose of ethanol and was on the same level after 3 and 8 hours. Its level decreased after 12 hours and was like in control group.